Analyzing research data on the use of L1 by teachers teaching non-linguistic subjects in a CLIL approach training context - Ilaria Salvadori (Firenze University Press, 2019)
The aim of this paper is to investigate teachers' perspectives on the use of the mother tongue (L1) in a Content and Language Integrated Learning (CLIL ) teaching context by teachers of non-linguistic subjects from upper secondary schools in Tuscany, involved in a training course conducted by the Department of Education, Languages, Interculture, Literature and Psychology, at the University of Florence. A seven-point questionnaire with a Likert scale was prepared in order to collect data concerning the following research questions: i) how often should L1 be used in the CLIL learning context; ii) how important is it to use L1 for the management of individual teaching activities. The intention is to contribute to the academic debate that has recently developed within this field of research, since the preparation of teachers through in-service training is a key to the effectiveness and sustainability of a CLIL approach.   Uso della L1 da parte di docenti di discipline non linguistiche in formazione metodologica CLIL: dati di una ricerca sul campo Lo scopo del presente contributo è quello di indagare la percezione riguardo l'utilità d'uso della lingua madre (L1) nel contesto di Content and Language Integrated Learning (CLIL) da parte di docenti di discipline non linguistiche di scuola secondaria di secondo grado della Toscana, impegnati in un corso di formazione metodologica tenuto presso l'università degli Studi di Firenze, dal Dipartimento Formazione, Lingue, Intercultura, Letterature e Psicologia. Per raccogliere questi dati è stato predisposto un questionario con scala Likert a sette gradi per rispondere alle due domande di ricerca iniziali: i) con quale frequenza si può usare la L1 nel contesto di apprendimento CLIL; ii) quanto è importante usare la L1 per la gestione di singole attività didattiche. Si intende in tal modo contribuire al dibattito accademico che ha mostrato recentemente interesse per questo settore di ricerca, convinti che la preparazione degli insegnanti tramite in-service training sia una chiave per l'efficacia e sostenibilità dell'approccio CLIL.